A Model for Determining Least-Cost Quail Stocking Programs - Charles H. Lobdell; Robert H. Giles Jr. (National Quail Symposium Proceedings, 2017)
A model is presented to allow the calculation of the minimum cost of providing an acceptable level of quail hunter success expressed as kill per day. The model is based on a Poisson distribution for hunter kill per day, the number of hunters, their success rates, quail survival rates, various costs of quail production and release, stocking levels, and frequency of stocking. An example is given.